MAQASID SYARI’AH DAN LINGKUNGAN HIDUP (Bahtsul Masa’il Sebagai Perlawanan Kaum Santri Terhadap Eksploitasi Pertambangan Emas di Silo Jember) - Ramadhan, Muhammad (Program Pascasarjana UIN Sumatera Utara, 2019)
Abstract: Nature is something that encompasses everything that exists on this earth naturally whetherliving or not, the worsening of the natural conditions requires humans to continue to preserve it, especiallyon the environment. environmental preservation is a matter of necessity for humans who are giventhe title of God as the caliph of the ard, so it is necessary to maintain cosmosentris human intervention.This paper is a paper through library research (Field Research) and field (Field Research), the themeraised is the shariah maqasid and the environment: bahtsul masa?il as the resistance of the studentsagainst the exploitation of gold mining in Silo Jember. There are three questions in this paper. First,what is the concept of Maqasid Shari?ah in protecting the environment? second, what are the views ofulama ?and santri towards the exploitation of gold mining in Silo? third, what is the impact of thecontribution of Ulama and santri views in the bahsul masail on the silo community related to goldmining? by using descriptive analytical methods the results of this paper are, first, to know the conceptof maqasid shari?ah in the environment. secondly, knowing the opinions of ulama ?and santri on theexploitation of gold mining in Silo village. third, provide a Sharia legal footing to the Silo communitytowards Gold Mining in the village of Silo, Jember Regency.Key Word : Mining Gold, Maqashid Syariah, Silo, Jember